Impact of academic fairs on the development of the entrepreneurial spirit of university students in Panama: Pre-pandemic period 2014-2019 - Barreto , Gustavo Adolfo Quintero (Seven Editora, 2024)
This research work analyzes the impact of initiatives associated with academic fairs of entrepreneurs to contribute to the development of the innovative spirit of Panamanian university students (period 2015-2019). These fairs have been taking place since 2015 in several universities in Panama and in one that served as a reference for this study, recording that until December 2019 at least 15 academic fairs of entrepreneurs had been developed in the latter, where students, professors and invited professionals participated as evaluation juries. of the projects presented. The academic activity of the fair is transversal to the curriculum in these universities and other areas such as university extension and very specifically the University Research Center also participate, with the growth from 2015 to 2019 being 91% in entrepreneurship projects, 86% in participating students and 79% in professors linked to the project (in the university center of reference for this report). The formulation of the problem for this type of study points us to the following: What is the impact of the entrepreneur fair on the development of the entrepreneurial spirit of the students of the reference University during the period 2014-2019? Additionally, the general questions of this Research focus on: How is the evolution of the entrepreneur fair from the period 2014 to 2019? and: What is the role of the teacher in the development of the entrepreneurial spirit of the students? and What are the acquired characteristics associated with the entrepreneurial spirit of the student who participates in these academic fairs of entrepreneurs? DOI:https://doi.org/10.56238/sevened2024.007-025